A cell-free assay for the insertion of a viral glycoprotein into the plasma membrane (The Rockefeller University Press, 1986)
A cell-free assay has been developed for the delivery of influenza virus neuraminidase to the plasma membrane. Two types of postnuclear supernatant, which acted as donor and acceptor of the enzyme, were prepared from baby hamster kidney cells. Donor preparations were obtained from cells infected with influenza virus and containing neuraminidase en route to the plasma membrane. Acceptor preparations were obtained from cells containing, bound to their plasma membranes, Semliki Forest virus with envelope glycoproteins bearing [3H]N- acetylneuraminic acid. Fusion between vesicles from these two preparations permits access of the enzyme to its substrate, which results in the release of free [3H]N-acetylneuraminic acid. This release was detected through the transfer of radioactivity from a trichloroacetic acid-insoluble to a trichloroacetic acid-soluble fraction. An ATP-dependent component of release was found, which appears to be a consequence of vesicle fusion. This component was enhanced when the donor was prepared from cells in which the enzyme had been concentrated in a compartment between the Golgi complex and the plasma membrane, which indicates that a specific exocytic fusion event has been reconstituted. The extent of fusion is greatly reduced by pre- treatment of donor and acceptor preparations with trypsin, which points to the involvement of proteins in the fusion reaction.